Surface-related high school football game injuries on pad and no-pad fields - Meyers, M. C. (The American Journal of Sports Medicine, 2021)
Background: Artificial turf fields are increasingly being installed with lighter weight infill systems that incorporate a pad underlayer, which is reported to reduce surface shock and decrease injuries. At this time, the effects of a pad underlayer on football trauma are unknown.